Upaya Meningkatkan Hasil Belajar dengan Menggunakan Pendekatan Pembelajaran Hitung-Menghitung PAUD Azzahra Kalideres Jakarta Barat - Yusty Yusty; Joni Tesmanto (Neolectura, 2021)
There are so many lessons to be learned in PAUD. One of them is counting lessons. Because counting lessons are considered quite difficult and uninteresting, this causes children's learning outcomes to be low. For this reason, teachers must familiarize children with learning to count through an approach to learning to count. This research is a survey research with a qualitative approach. This research was conducted in the Azzahra Kalideres PAUD, West Jakarta. The research was carried out for 3 months, consisting of the preparation of proposals, testing of instruments, dissemination and collection of field research data, preparation and processing of data. The research was conducted in January–March 2018. Data collection was done through interviews and documentation from the literature study. The results of the study show that learning to count counting must be linked to the real world in order to make it easier for children to learn mathematics. With the help of the teacher, children are given the opportunity to discover mathematical concepts for themselves. After that, they have to apply it in their daily life or in other fields.